Ionic Mechanisms of Burst Firing in Dissociated Purkinje Neurons - Swensen, Andrew M. (J Neurosci, 2003)
Cerebellar Purkinje neurons have intrinsic membrane properties that favor burst firing, seen not only during complex spikes elicited by climbing fiber input but also with direct electrical stimulation of cell bodies. We examined the ionic conductances that underlie all-or-none burst firing elicited in acutely dissociated mouse Purkinje neurons by short depolarizing current injections. Blocking voltage-dependent calcium entry by cadmium or replacement of external calcium by magnesium enhanced burst firing, but it was blocked by cobalt replacement of calcium, probably reflecting block of sodium channels. In voltage-clamp experiments, we used the burst waveform of each cell as a voltage command and used ionic substitutions and pharmacological manipulations to isolate tetrodotoxin (TTX)-sensitive sodium current, P-type and T-type calcium current, hyperpolarization-activated cation current (I(h)), voltage-activated potassium current, large-conductance calcium-activated potassium current, and small-conductance calcium-activated potassium (SK) current. Measured near the middle of the first interspike interval, TTX-sensitive sodium current carried the largest inward current, and T-type calcium current was also substantial. Current through P-type channels was large immediately after a spike but decayed rapidly. These inward currents were opposed by substantial components of voltage-dependent and calcium-dependent potassium current. Termination of the burst is caused partly by decay of sodium current, together with a progressive buildup of SK current after the first interspike interval. Although burst firing depends on the net balance between multiple large currents flowing after a spike, it is surprisingly robust, probably reflecting complex interactions between the exact voltage waveform and voltage and calcium dependence of the various currents.